NURSING IN INTENSIVE CARE PATIENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Intensive care nurses are a new stage in the healthcare system today, playing an important role in improving the quality of primary health care. Their professional training, level of qualification and ability to work independently directly affect the quality of medical care. This article analyzes the extensive work and advanced experience in this area, and once again emphasizes that the clinical training of nurses, their theoretical and practical skills, compliance with sanitary and safety rules, and their communicative and psychological training are essential for this field to open the door to practical and theoretical knowledge in order to provide adequate assistance to the lifestyle and health of the population.